RELATIONSHIP BETWEEN MICRONUTRIENT INTAKE AND HEMOGLOBIN LEVELS IN PREGNANT WOMEN IN DEPOK CITY WEST JAVA - Fikriah, Sinta Aulia; Nurbaeti, Irma (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background: Anemia remains a public health issue among pregnant women in Indonesia, including in the city of Depok. One of the causes is insufficient intake of micronutrients such as iron, folic acid, vitamin B12, and vitamin C, which play a crucial role in hemoglobin production. Objectives: This study aims to investigate the relationship between micronutrient intake and hemoglobin levels among pregnant women Methods: This study employed a cross-sectional design in Depok city, West Java, in April to May 2025. A sample of 107 pregnant women was selected using accidental sampling. Data were collected through interviews using a 24-hour Dietary Recall questionnaire and hemoglobin level test results from medical records. The Spearman Rank test was used for data analysis Results: The results showed that the majority of respondents had an adequate intake of micronutrients (81.3%) and hemoglobin levels in the non-anemic category (70.1%). A significant association was found between iron, folic acid, vitamin B12, and vitamin C intake and hemoglobin levels (p = 0.0001). A history of anemia was also strongly associated with hemoglobin levels (p = 0.0001; r = 0.706). Conclusion: Adequate intake of iron, folic acid, vitamin B12, and vitamin C plays a role in maintaining hemoglobin levels in pregnant women. Nutrition education and monitoring of micronutrient intake need to be improved in nursing practice to prevent anemia and pregnancy complications.